2015
DOI: 10.1007/s10120-015-0519-7
|View full text |Cite
|
Sign up to set email alerts
|

Programmed cell death protein 1 expression is an independent prognostic factor in gastric cancer after curative resection

Abstract: PD-1 expression is associated with a poor prognosis and is correlated with PD-L1 and Foxp3 expression in patients with gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
132
3
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(151 citation statements)
references
References 25 publications
6
132
3
4
Order By: Relevance
“…However, for patients with GC, the association between the expression of PD-L1 and their prognosis remains controversial. Multiple studies have indicated that positive PD-L1 expression is associated with a significantly poor OS1617181920212223, but other studies could not confirm this finding2425.…”
Section: Discussionmentioning
confidence: 99%
“…However, for patients with GC, the association between the expression of PD-L1 and their prognosis remains controversial. Multiple studies have indicated that positive PD-L1 expression is associated with a significantly poor OS1617181920212223, but other studies could not confirm this finding2425.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies on gastric carcinoma utilizing immunohistochemistry (IHC) for PD-L1 demonstrated varying rates of PD-L1 expression, ranging from 5.1% to 65.0% [1626]. In the majority of studies, PD-L1 expression was associated with an unfavorable prognosis [1622, 25, 26]; however, recent studies have linked PD-L1 expression with a favorable prognosis [23, 24]. …”
Section: Introductionmentioning
confidence: 99%
“…Since it is difficult to get fresh specimens from patients to determine the expression of PD-1 or PD-L1 expression by IHC, no uniform standard was defined for PD-L1 positivity up to now. Eto et al defined PD-L1 positivity by staining of the tumor-cell in four grade: 6–25, 26–50 or 51–75 and 76–100% of cells (12,2329); Ti Wen and co-worker defined staining pattern of PD-L1 as positive if <5 or ≥5% in tumor cells (13); whereas Wenfeng Fang assessed the expression of PD-L1 by semi-quantitative H-score and defined cases with greater than 10% PD-L1 expression on tumor cells were considered positive (26). Therefore, consistency detection of PD-1 and PD-L1 expression by IHC is limited due to the difference of antibody qualities from different manufacturers, the interpretative subjectivity, and the different standard on positivity thresholds.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion criteria were listed as follows: i) The diagnosis of metastatic gastric cancer was confirmed by endoscopic biopsy and imageological examination; ii) the disease was classified as pathologic M1 with any T and N stage based on the standard of the WHO Classification of Tumors of the Digestive System, 2010 edition (12,13); iii) 2 ml peripheral blood was drawn before the first line therapy; iv) patients had completed 4 courses of first line chemotherapy as documented in the medical record; and v) complete follow-up data was available. This study was approved by the ethics committee at the Zhengzhou University Affiliated Cancer Hospital, and informed consent form was signed by every patient.…”
Section: Methodsmentioning
confidence: 99%